Metabolic Syndrome in psoriasis: a hospital based cross-sectional study in Central India - Singh Bhati, Surendra; Shah, Akhil; Chaudhary, Subhash; Kumar, Saket; Tomar, Anushtha; Jain, Shubhang (International Journal of Medical Research and Review, 2019)
Background: Psoriasis is a chronic immune-mediated inflammatory disorder, reported to be associated with obesity, dyslipidaemia and diabetes via common immunological mechanisms. All of these components ultimately increase the risk of metabolic syndrome and cardiovascular morbidities. Aims and Objectives: To assess the association of Metabolic Syndrome (MS) and its components in patients suffering from psoriasis. To study the relationship between the duration and severity of psoriasis and MS. Materials and Methods: A hospital based cross-sectional study was conducted involving 100 adult patients with psoriasis and 100 controls. All participants were evaluated forpsoriasis and the components of MS. Psoriasis was categorized as mild, moderate and severe based on Psoriasis Area and Severity Index (PASI) (<7, 8–12 and >12, respectively). In all patients and controls, body mass index was calculated, blood pressure and waist circumference were measured and fasting blood sugar and lipid profile were estimated. Results: In the present study, a higher prevalence of MS in Psoriasis patients than in controls (38% v/s 23%) was observed. Psoriatic patients had higher prevalence of hypertension (36% v/s 14%). It can be concluded that association of MS and psoriasis is independent of the type, duration and severity of psoriasis. Conclusion: The present study suggests that subjects with psoriasis present a greater risk of MS and should trigger a higher clinical suspicion for their co-existence. Psoriasis is a systemic disease with significant morbidity and mortality. This study emphasizes the critical need for providers to screen psoriasis patients for early diagnosis and treatment of associated MS. However, more number of large population based cohort studies are required to establish stronger association between psoriasis and MS.